Analisis Penerapan Standar Keselamatan dan Kesehatan Kerja pada Pelayanan Antenatal Care: (Literatur Review) - Waldatul Hamidah; Nelmi Silvia (Institut Nalanda, 2026)
Background: The implementation of Occupational Health and Safety (OHS) standards in antenatal care (ANC) services is a critical requirement to protect both patients and healthcare workers. Despite regulatory mandates, compliance levels across health facilities remain inconsistent. Objective: This literature review aims to analyze OHS standard implementation in ANC services, identify influencing factors, existing barriers, and formulate evidence-based strategic recommendations. Method: A systematic literature search was conducted across Google Scholar, PubMed, and Portal Garuda, covering publications from 2020 to 2024. Twenty-five articles were selected based on predetermined inclusion criteria. Results: OHS implementation in ANC encompasses three primary domains: infection prevention and control (62-89%), ergonomic risk management (45-70%), and patient and staff safety (55-80%). Key determinants include management support, staff competency, infrastructure availability, and institutional OHS culture. The COVID-19 pandemic significantly accelerated improvements in infection control protocols but simultaneously reduced ANC visit rates. Conclusion: Strengthening OHS standards in ANC requires a multilevel approach integrating policy reform, institutional commitment, and individual capacity building.